Small Molecule Rescue and Glycosidic Conformational Analysis of the Twister Ribozyme - Messina, Kyle J. (Biochemistry, 2019)
The number of self-cleaving ribozymes has increased sharply in recent years giving rise to elaborations of the four known ribozyme catalytic strategies α, β, γ, and δ. One such extension is utilized by the twister ribozyme, which is hypothesized to conduct δ, or general acid catalysis, via N3 of the syn adenine +1 nucleobase indirectly via buffer catalysis at biological pH and directly at lower pH. Herein, we test the δ catalysis role of A1 via chemical rescue, and the catalytic relevance of the syn orientation of the nucleobase by conformational analysis. Using inhibited twister ribozyme variants with A1(N3) deaza or A1 abasic modifications, we observe chemical rescue effects greater than one hundred-fold in the presence of protonatable biological small molecules such as imidazole and histidine, similar to observed rescue values previously reported for C75U/C76Δ in the HDV ribozyme. Brønsted plots on the twister variants support a model in which small molecules rescue catalytic activity via a proton transfer mechanism, suggesting that A1 in the wild-type is involved in proton transfer, most likely general acid catalysis. Additionally, through glyosidic conformational analysis in an appropriate background that accommodates the bromine atom, we observe that an 8BrA1-modified twister ribozyme is up to 10-fold faster than a non-modified A1 ribozyme supporting crystallographic data that A1 is syn when conducting proton transfer. Overall, this study provides functional evidence that the nucleotide immediately downstream of the cleavage site participates directly or indirectly in general acid-base catalysis in the twister ribozyme while occupying the syn conformation.